Studi Analisis Isi Komunikasi Islam Habib Husein Al Hadar Di Youtube - Amarullah, Rafli Husein; Saepulloh, Uwoh (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This paper aims to find out the Islamic communication of Habib Husein Ja'far Al Hadar in the da’wah video on Youtube Jeda Nulis as peace journalism which consists of four aspects, namely, the content of tabligh (information), taghyir (change), akhlak al-karimah (noble behavior), and khairu ummah (the best people). The research method using content analysis aims to provide insight and knowledge about how Islamic communication from Habib Hussein on Youtube. The approach used is a qualitative approach. The results showed that the Islamic communication carried out by Habib Hussein in each of his da’wah videos was peace journalism, containing an Islamic tabligh full of love, spirituality, humanity, tolerance, and rationality that encouraged mad’u to do taghyir to become a better person (khairu ummah) by behaving noblely and lovingly (akhlak al-karimah).